2021
DOI: 10.1249/mss.0000000000002789
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Upper Quadrant Musculoskeletal Injuries in the Military: A Cohort Study

Abstract: Purpose: This study aimed to identify characteristics and movement-based tests that predict upper quadrant musculoskeletal injury (UQI) in military personnel over a 12-month follow-up. Methods: A prospective observational cohort study of military members (n = 494; 91.9% male) was conducted. Baseline predictors associated with UQI were gathered through surveys and movement-based tests. Survey data included demographic information, injury history, and biosocial factors. Movement-based tests include the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 36 publications
(77 reference statements)
0
16
3
1
Order By: Relevance
“…A maximum superolateral (SL) reach distance of ≤80.1% arm length (AL) as well as an inferolateral (IL) reach asymmetry of ≥7.75% AL was found to increase the likelihood of a future time-loss injury. Further, specific cut-off values for military personnel ( N = 494, m = 454, f = 40; age: 28.6 ± 6.8 years) were reported by Campbell et al ( 22 ). In this study, the authors identified an SL reach distance of ≤57.75 cm and a composite score (CS) of less than ≤81.1% AL in the YBT-UQ as risk factors for suffering an upper quadrant musculoskeletal injury.…”
Section: Introductionmentioning
confidence: 78%
“…A maximum superolateral (SL) reach distance of ≤80.1% arm length (AL) as well as an inferolateral (IL) reach asymmetry of ≥7.75% AL was found to increase the likelihood of a future time-loss injury. Further, specific cut-off values for military personnel ( N = 494, m = 454, f = 40; age: 28.6 ± 6.8 years) were reported by Campbell et al ( 22 ). In this study, the authors identified an SL reach distance of ≤57.75 cm and a composite score (CS) of less than ≤81.1% AL in the YBT-UQ as risk factors for suffering an upper quadrant musculoskeletal injury.…”
Section: Introductionmentioning
confidence: 78%
“…Sample size is a key design feature in prediction model studies; obtaining a suitable sample size is important to mitigate against overfitting. The authors opaquely performed a sample size calculation using Monte Carlo Simulation with 450 participants and ultimately assessed 45 variables (1). Sample size calculations for developing a prediction model should be based on outcome prevalence, the number of parameters, level of shrinkage (measure of overfitting, higher values implying less overfitting), and anticipated overall model fit ( R 2 ) (8).…”
mentioning
confidence: 99%
“…Our motivation is not to critique the time and effort undertaken by the authors (1), but rather help improve the model, as prediction models can have direct effect on patient health. We would be interested in collaborating to improve these models and ultimately patient care.…”
mentioning
confidence: 99%
“…The backward approach selected the same variables and detected the same number of upper quadrant injuries (12/27, or 44.4%) as our forward selection for a prediction accuracy of 83%. Bootstrap coefficient estimates for selected variables remained as published (2). Finally, we acknowledge that dichotomizing continuous predictors for clinical simplicity can lead to information loss and may limit prediction performance (6).…”
mentioning
confidence: 99%
“…Also, a univariate filtering strategy presents limitations (6). Nevertheless, after applying this strategy and eliminating variables presenting collinearity or limited theoretical relevance, we only entered five history/personal characteristics, two pain provocation, and two movement-based variables in the multivariable analysis (2). Overfitting is still possible given the number of predictors considered, albeit much lower than suggested in the letter (1).…”
mentioning
confidence: 99%